Clinical, biochemical, and immunohistochemical features of necrobiotic xanthogranulomatosis. Issue 1 (1st January 2003) - Jeziorska, M; Hassan, A; Mackness, M I; Woolley, D E; Tullo, A B; Lucas, G S; Durrington, P N
Abstract : Aims: To describe the clinical features of two patients with paraproteinaemia and necrobiotic xanthogranulomatosis together with detailed immunohistochemistry of the lesions in one. Methods: The clinical history and results of biochemical investigations of the patients were retrieved from the files. Immunohistochemistry was used to investigate the expression of macrophage and mast cell markers, amyloid A and P, S-100 protein, and apolipoprotein AI and B in xanthogranulomatous skin lesions from patient 2. In addition, protein A–sepharose chromatography was used to separate serum from patient 2 and apolipoprotein B and the IgG paraprotein were measured in the fractions eluted. Results: Monocytes/macrophages comprised the major cellular component of the lesion, and unusually for xanthomata, areas of collagen necrosis were also seen. Activated mast cells were present at the margins of macrophage clusters and adjacent to areas of collagen necrosis. Serum paraprotein was bound to low density lipoproteins as judged by protein A–sepharose chromatography, and was also located within macrophagic foam cells of the lesion on immunohistochemistry. Conclusions: These observations demonstrate many features similar to atherosclerosis including collagen necrosis and mast cell activation.